Characteristics and risk factors of fever after total joint arthroplasty: a single-center retrospective study - MingYang Li; ChengYu Lyu; Yuan Fang; ZhenShuai Shao; Kun Liu; Ning Liu (BMC Musculoskeletal Disorders, 2022)
Abstract Background Postoperative fever (POF) is a common problem after total joint arthroplasty (TJA). The goal of this research is to analyze the characteristics and risk factors of fever following TJA. Methods We retrospectively investigated 2482 patients who had primary total knee arthroplasty (TKA) or total hip arthroplasty (THA) surgery at our institution between January 2020 and December 2020. Those patients were divided into TKA group and THA group. The patients' axillary temperatures were measured. POF was defined as a body temperature greater than 38 °C. Then patients in the TKA and THA groups were respectively divided into afebrile group and febrile group based on their body temperatures. Temperature changing characteristics of the patients in the febrile group were analyzed and recorded. According to the number of patients in the febrile group, we randomly selected a corresponding number of patients from the afebrile group at a ratio of 1:2 to establish a control group. Gender, hypertension, diabetes, anesthesia, surgical time, and some laboratory data were analyzed between the febrile group and the afebrile group. Results Three percent of TKA patients (N = 45) had febrile, and in the febrile group of TKA group, 38% (N = 17) had fever and maximum body temperature on postoperative day 2(POD2). Six percent of THA patients (N = 46) had fever, and in the febrile group of THA group, 65% (N = 30) of the patients had fever and maximum body temperature on POD1. In TKA group, compared with afebrile group, febrile group has higher C-reactive protein (mg/L) (CRP) after surgery. In THA group, compared with the afebrile group, the patients in the febrile group had larger fall in hemoglobin (g/L), and higher C-reactive protein (mg/L) (CRP) after surgery, so there were statistically significant differences between the two groups (P < 0.05). Conclusion The POF rate of TKA is 3%, and the first fever and maximum body temperature most commonly appear on the POD2. THA has a 6% POF rate, and the first fever and the maximum body temperature most commonly appear on the POD1. In both groups, high C-reactive protein is a risk factor for postoperative fever. In addition, the fall in hemoglobin is also related to postoperative fever in the THA group.